The Behavior of RC Beams Strengthened with Steel Fiber Concrete Layer by ANSYS Simulation - Thanh Quang Khai Lam; Thi My Dung Do (Advances in Civil Engineering)
In this study, a double-layer reinforced concrete beam structure was created for the purpose of repairing reinforced concrete beams by pouring a layer of concrete on top of the reinforced concrete beam and then adding fibers to the concrete. Take into consideration the bearing capacity of these double-layer concrete beams as well as the effects that the input parameters have on the stress strain, the propagation of cracks in reinforced concrete beams. The study looks at double-layered reinforced concrete beams, with the steel fiber concrete placed on top of the one containing the normal concrete. This investigation led to the following relationships: load-compressive stress, tensile stress, and vertical displacement at the midpoint of the beam span, as well as a diagram showing how cracks spread in the beams. After getting the experimental results and comparing them with an ANSYS simulation, the diagram was used to figure out the loads at which the beams start to look cracked and the loads at which the beams are damaged. This study investigated the following six cases: how the addition of SFs affects the properties of concrete, the spacing of the stirrups at the ends of the beam should be looked into to see what effects it might have, how the number of tensile steel bars in the beam affects its properties, how the diameter of tensile steel bars affects their properties, how the diameter of compressed steel bars affects the results, and how the thickness of the SFC layer affects the properties of the material. Also, the things that were mentioned would have a big effect on how these double-layer beams in the design work.